Reply to ’Novel Drug Targets Based on Association between Inflammation and Pancreatic Ductal Adenocarcinoma’ - Uomo, Ilaria; Miraglia, Simona; Pastorello, Maurizio (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Logo of "Provincial Health Unit". Palermo, Italy.